Association of HLA-DRB1/DQB1 polymorphism with high-risk HPV infection and cervical intraepithelial neoplasia women from Shanghai - Zhao, Junwei (Int J Clin Exp Pathol, 2018)
Persistent human papillomavirus (HPV) infection is the main causative agent for cervical intraepithelial neoplasia (CIN) and cancer. Variability in host immunogenetic factors is important in determining the overall cellular immune response to the HPV infection. This study was carried out to confirm the association of human leukocyte antigen (HLA) class II DRB1 and DQB1 alleles with CIN and HPV persistent infections in women from Shanghai in a case-controlled study. A total of 170 patients, including 105 HPV positive patients and 65 HPV negative women (control) participated in the study. HybriBio’s proprietary flow-through hybridization technique was used to perform HPV genotyping. Low-resolution PCR-sequence specific priming (PCR-SSP) was used to genotype HLA class II for DRB1 and DQB1 loci. Binary and multivariate logistic regression analysis highlighted the association of specific alleles with CIN and HPV persistent infections after adjusting for the confounding factor of age. HLA-DQB1*02 and *06 is significantly associated with increased risk of HPV16 persistent infection (P (c) < 0.013). HLA-DRB1*09 is significantly associated with increased risk for CIN, whereas the -DRB1*16 exhibit protective to CIN (P < 0.05). Significant association is found for HLA-DQB1*04 and *06 with increased risk for CIN (P < 0.05). There were possible associations of specific HLA class II alleles either with risk of persistent HPV infection or with developing CIN.